With your words in my hands : the letters of Antonietta Petris and Loris Palma - Petris, Antonietta; Palma, Loris, -2007; Cancian, Sonia, 1965-; Cancian, Sonia, 1965- (McGill-Queen's studies in ethnic history., 2021)
"Following Antonietta and Loris's first kiss in the shadows of the Italian Alps barely a year after the end of the Second World War, the couple's courtship was separated by a distance far greater than could ever have been imagined. With Antonietta's family moving to Montreal, migration entered the couple's intimate worlds, shifting the distance between them from their hometowns of Ampezzo and Venice to Montreal and Venice. Throughout their transatlantic separation, the young lovers fervidly wrote each other until they were reunited in Canada in 1949. With Your Words in My Hands tells a story about love and migration as written and read, idealized and imagined, through daily correspondence. Sonia Cancian recovers a rare complete epistolary record of an immigrant experience defined by love and sustained in writing, translating the letters with deftness and an ear for the immediacy of emotion and longing they embody. Cancian gives context to these exchanges dating from the beginning of the largest migration movement from Italy to Canada, showing how love, frustration, fear, sadness, and empathy were palpable elements that inflected the quotidian--bureaucratic processes, employment, family life--and defined immigrant experience. For the countless couples whose love is fragmented by separation but woven together with envelopes and stamps, or onscreen in today's instant messaging, these letters remind us how the experience of distance and proximity, absence and presence, can be reconfigured within the world of intimate correspondence."--